Physics and Metaphysics in an Early Ottoman Madrasa: Dāwūd al-Qayṣarī on the Nature of Time - Todd, Richard (Oriens, 2022)
Although overshadowed by his celebrated commentaries on Ibn ʿArabī and Ibn al-Fāriḍ, Dāwūd al-Qayṣarī’s (d. 750/1351) treatise on the philosophy of time – the Nihāyat al-bayān fī dirāyat al-zamān (The Utmost Elucidation Concerning Knowledge of Time) – is a notable milestone in the history of Islamic conceptions of temporality. Composed around the start of Qayṣarī’s tenure as head of the first Ottoman madrasa, the Nihāyat al-bayān rejects the Aristotelian definition of time as the number of motion in favor of Abū l-Barakāt al-Baghdādī’s concept of zamān as the measure of being. Challenging, likewise, portrayals of time as a flux or succession of fleeting instants, Qayṣarī propounds instead an absolutist vision of time as an integral, objectively existent whole. Qayṣarī’s reassessment of dominant medieval theories of temporality – including kalām atomism and the Neoplatonic distinction between time, perpetuity, and eternity – is thus shown to be a key early example of what was to become an abiding Ottoman interest in time and timekeeping.